SELF-MICROEMULSIFYING DRUG DELIVERY SYSTEM - Anand, Sonia; Gupta, Rishikesh; Sk, Prajapati (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Oral route is the most convenient route of drug administration in many diseases and till today it is the first way investigated in the development of new dosage forms. The major problem in oral drug formulations is low and erratic bioavailability, which mainly results from poor aqueous solubility, thereby pretense problems in their formulation. More than 40% of potential drug products suffer from poor water solubility. For the therapeutic delivery of lipophilic active moieties (biopharmaceutical classification system Class II drugs), lipid-based formulations are inviting increasing attention. Currently, a number of technologies are available to deal with the poor solubility, dissolution rate, and bioavailability of insoluble drugs. One of the promising techniques is self-microemulsifying drug delivery systems (SMEDDS). SMEDDS have gained exposure for their ability to increase solubility and bioavailability of poorly soluble drugs. SMEDDS, which are isotropic mixtures of oils, surfactants, solvents, and co-solvents/surfactants can be used for the design of formulations to improve the oral absorption of highly lipophilic drug compounds. Conventional SMEDDS are mostly prepared in a liquid form, which can have some disadvantages. SMEDDS can be orally administered in soft or hard gelatin capsules and form fine relatively stable oil-in-water emulsions. Solid-SMEDDS are prepared by solidification of liquid/semisolid self-micron emulsifying ingredients into powders, have gained popularity. This article gives a complete overview of SMEDDS, but special attention has been paid to formulation, design, evaluation, and little emphasis on application of SMEDDS. Keywords: Self-microemulsifying drug delivery system, Surfactant, Oil, Co-surfactant, Bioavailability, Lipophilic, Biopharmaceutical classification system Class II drugs.